2014
DOI: 10.1097/jsm.0000000000000054
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Nutritional Knowledge, and Eating Behaviors in Elite Student and Professional Ballet Dancers

Abstract: The findings suggest that dancers with disordered eating also display lower levels of nutritional knowledge, and this may have an impact on BMI. Female students' eating attitudes and BMI should especially be monitored during periods of adolescent development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 22 publications
1
33
2
3
Order By: Relevance
“…In this regards our results do not confirm that dancers are more similar to eating-disordered individuals than to control individuals on measures of eating pathology (2). With respect to the BMI, Wyon et al (35) have reported that professional dancers had significantly greater BMI than student dancers, so a low BMI as risk factor for ED among dancers seems to remain controversial. Apart from the different cut-off point there is a factor, which could have influenced on our results.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In this regards our results do not confirm that dancers are more similar to eating-disordered individuals than to control individuals on measures of eating pathology (2). With respect to the BMI, Wyon et al (35) have reported that professional dancers had significantly greater BMI than student dancers, so a low BMI as risk factor for ED among dancers seems to remain controversial. Apart from the different cut-off point there is a factor, which could have influenced on our results.…”
Section: Discussioncontrasting
confidence: 55%
“…These facts, along with a bit different mean age with respect to the reported in other articles must be taken into account for future studies: in our case 21.22 while other studies report, for example, 13-20 years old (4) or 25 years old (9). In fact, Wyon et al (35) reported higher EAT-26 scores for female ballet dancers in years 10 and 12. So our first hypothesis was partially confirmed when we used the cut-off point of 21 with respect to the EAT-40.…”
Section: Discussionmentioning
confidence: 99%
“…Although dance is a performing art by nature, the physiological demands suggest dancers are athletes as well as artists. Dance requires technical skill, strength, and endurance, all of which place great demands on the dancer [2]. In order to meet these demands while maintaining the necessary aesthetic, optimal nutrition is of primary importance [2].…”
Section: Introduction mentioning
confidence: 99%
“…A study showed that learning, understanding and applying nutritional knowledge increased with aged and that dancers become more aware of healthy eating habits as they past puberty. 8 The female body changes very often throughout puberty and reaches sometimes until college. Participants agreed that in the first year of college it is hard to adjust eating habits and meals because of the food choices on and off campus.…”
Section: Resultsmentioning
confidence: 99%